B cell responses to conjugate and polysaccharide meningococcal vaccines - Ramasamy, M (2012)
The primary approach to the control of meningococcal disease remains effective vaccination programmes in susceptible populations. Vaccines against serogroups A, C, W and Y offer broad protection against meningococci and both polysaccharide and conjugate quadrivalent vaccines are licensed for use in the UK. Previous studies have assessed the antibody response to meningococcal polysaccharide and conjugate vaccines, but there is limited information on the nature of the B cell response to these antigens. As part of a clinical trial using both polysaccharide (MenACWY-PS) and conjugate (MenACWY-CRM) vaccines in adult volunteers, this DPhil reports the analysis of subsets of antigen specific B-cells produced in response to either vaccine. Prior MenACWY-PS impaired the response to a subsequent dose of MenACWY-CRM. This may be due to MenACWY-PS driving terminal differentiation of antigen specific cells into plasma cells, without replenishment of the memory B cell pool. In addition, despite prior data indicating that it may act as a thymus dependent antigen, the serogroup A polysaccharide component of MenACWY-PS appears to behave in the same way as serogroup C, W & Y polysaccharide components. Antibody molecules recognise and bind to a multitude of conformational epitopes. This variability is enabled by the complexities of immunoglobulin variable domain gene recombination which can generate a vast potential repertoire of unique antibody molecules. However, the diversity of the antibody repertoire is more restricted against specific antigens and within defined B cell subsets. In this DPhil, ‘next generation’ sequencing technologies were used to investigate the diversity of the B cell variable domain before and after vaccination of adult volunteers. Individuals at baseline were found to have distinct antibody repertoires. Vaccination with a Haemophilus influenzae type b (Hib) conjugate vaccine resulted in an oligoclonal antibody response, with enrichment for Hib specific canonical antibody sequences.